Development possibilities of personal investments into financial instruments in Lithuania - Klimavičienė, Aušra; Jurevičienė, Daiva (Business: Theory and Practice, 2007)
The article examines the development possibilities of personal financial investments and the importance to induce those investments in Lithuania. The links between personal finance, financial assets and personal financial investments are analyzed. The development of Lithuanian stock market is reviewed and the investment opportunities are revealed. The paper analyses the results of investors survey, explores the reasons for not investing and not saving behavior and the ways to foster investments into securities and to increase population’s interest in security market. The investment knowledge, skills and decisions regarding the selection of financial tools are assessed and the ways to induce the investments into securities are introduced. The potential of personal financial investments development in Lithuania – based on results of analysis of research data - is evaluated, the effective solutions that might foster the popularity of personal financial investments in our country are proposed.Article in Lithuanian.Asmens investicijų į finansines priemones plėtros galimybės LietuvojeSantrauka. Straipsnyje nagrinėjamos asmeninių finansinių investicijų plėtros Lietuvoje problemos ir skatinimo investuoti svarba. Analizuojamas asmeninių finansų, finansinio turto, asmens finansinių investicijų ryšys. Daug dėmesio skiriama Lietuvos vertybinių popierių rinkos plėtrai apibendrinti, atskleidžiamos investavimo galimybės. Analizuojami investuotojų apklausos rezultatai, identifikuojamos neinvestavimo ir netaupymo priežastys, vertinamos gyventojų žinios, investavimo įgūdžiai, investicinių priemonių pasirinkimo sprendimai, pateikiama siūlymų dėl investicijų į vertybinius popierius skatinimo. Remiantis tyrimo duomenų analizės rezultatais, vertinamas asmeninių finansinių investicijų plėtros Lietuvoje potencialas, siūlomi efektyvūs sprendimai, galintys teigiamai veikti asmeninių finansinių investicijų populiarumą šalyje.Reikšminiai žodžiai: asmeniniai finansai, asmeninės finansinės investicijos, vertybinių popierių rinka, finansinis turtas, taupymas, finansinės priemonės.